Predictive models for thromboembolic events in giant cell arteritis: A US veterans health administration population-based study - Michailidou, Despina; Zhang, Tianyu; Kuderer, Nicole M.; Lyman, Gary H.; Diamantopoulos, Andreas P.; Stamatis, Pavlos; Ng, Bernard (Frontiers in Immunology, 2022)
Information related to this manuscript cannot be released until November 9th.